Perioperative ischaemia and management of patients with coronary stents: current practice - Pokharel, Jeju Nath (Journal of Society of Anesthesiologists of Nepal, 2015)
Perioperative ischaemia is a common cause of cardiac morbidity and cardiac death during perioperative period in patient with coronary artery disease or with other risk factors. The incidence of perioperative ischaemia is about 20 to 70% in patient with coronary artery disease or coronary artery disease risk factors. Post operative cardiac events (the combined incidence of nonfatal myocardial infarction, unstable angina, heart failure and sudden cardiac death) vary between 5.5 to 53% and postoperative myocardial infarction varies between 1.4 to 43%. Prolonged ST- segment depression along with hypercoagulability caused by surgical stress, platelet activation, increased fibrinogen activity and decreased fibrinolytic activities may lead to coronary thrombosis, ischaemia, nonfatal infarction or sudden cardiac death. Patients with coronary stents especially before complete endothelialization of the stents are of high risk category for these complications. Anesthesiologist being a perioperative physician should understand safety issues of these patients to prevent from ischaemia, coronary thrombosis and subsequent infarction or sudden cardiac death. Risk identification, optimization, monitoring, diagnosis of the problem, prevention and management are very crucial during perioperative period to enhance the quality service and patient safety. Journal of Society of Anesthesiologists 2014 1(1): 40-48